(untitled) (Progressive Agriculture, 2016)
An experiment was carried out at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh during June to December 2012 with a view to finding out the impact of variety and levels of nitrogen on the growth performance of transplant Aman rice. The experiment comprised four varieties viz. BRRI dhan33, BRRI dhan34, BRRI dhan39 and BRRI dhan46, and four levels of nitrogen viz. control (no urea), prilled urea (50 kg N ha-1), one pellet (0.9g) of USG/4 hills of two adjacent rows (30 kg N ha-1) was applied at 10 days after transplanting (DAT) and two pellets of USG (0.9g each) one applied at 10 DAT and the another at 45 DAT/4 hills of two adjacent rows (60 kg N ha-1). The experiment was laid out in a randomized complete block design with three replications. Results of the experiment showed that variety and levels of nitrogen had significant effect on plant height, number of tillers hill-1 and leaf area index (LAI) of HYV transplant Aman rice. At 15 and 75 DAT the tallest plant was found in BRRI dhan34 whereas at 30, 45 and 60 DAT the tallest plant was found in BRRI dhan39. BRRI dhan34 produced higher number of tillers hill-1 at 75 DAT which was as good as BRRI dhan33 and BRRI dhan46 while BRRI dhan39 produced higher LAI in compare to other varieties at all sampling dates. Two pellets of USG (0.9g each) one applied at 10 DAT and the another at 45 DAT/4 hills of two adjacent rows (60 kg N ha-1) can produced tallest plant, higher number tillers hill-1 and higher LAI at all dates of sampling. Among the interaction BRRI dhan34 fertilized with two pellets of USG (0.9g each) one applied at 10 DAT and another at 45 DAT/4 hills of two adjacent rows (60 kg N ha-1) appears as the promising combination in respect of growth performance of HYV transplant Aman rice. Progressive Agriculture 27 (1): 32-38, 2016